An evaluation of the prevalence of autoimmunological diseases in patients with diabetes and obesity hospitalized in the Department of Diabetology, Rural Medicine Institute in Lublin - Szcześniak, Grzegorz Roman; Zdybel, Wojciech; Kozak-Nurczyk, Patrycja; Dziemidok, Piotr (Family Medicine & Primary Care Review, 2016)
Background. Type 1 diabetes often coexists with other diseases conditioned autoimmunologically. Objectives . An assessment of the coexistence of autoimmune diseases in patients with type 1 diabetes in relation to their prevalence in people with type 2, secondary diabetes and obesity without diabetes. Material and methods. Analysis of the medical records of 937 patients hospitalized in the Diabetology Department: 203 with type 1 diabetes, 583 with type 2, 24 with secondary diabetes and 126 obese. Results . In patients with type 1 diabetes one additional autoimmune disease was found in 44 (22%), two in 7 (3%) – we diagnosed APS-3 in those cases. In 40 (20%) of them Hashimoto’s thyroiditis was found, in 5 (2%) – Graves’ disease, 6 (3%) – vitiligo, 4 (2%) – Addison-Biermer’s disease or celiac disease, in 2 (1%) rheumatoid arthritis. Sjögren syndrome, autoimmune vasculitis and stiff man syndrome we recognized in single men. In the type 2 diabetics two autoimmune diseases were found in 1 patient (0.2%) and one in 23 (4%). In the group of obese patients these kinds of diseases were found in 7 cases (6%). Among patients with secondary diabetes there were no autoimmune diseases. Hashimoto disease was also the most frequent autoimmune disease in the type 2 diabetes and obesity groups: 17 subjects (3%) and 6 (5%), respectively. Conclusions . We should actively look for other autoimmune disease in patients with type 1 diabetes. Also, we cannot forget that they can also occur in patients with type 2 diabetes and isolated obesity.